The Family Psychoeducation to Improve Parents' Coping Strategies in Caring for Thalassemia Children - Mariani, Dini; Muffidah, Annisa Salwa; Rosdiana, Ida (Poltekkes Kemenkes Palu, 2023)
Thalassemia is a genetic disorder of the synthesis of alpha or beta globin chains, either in whole or in part. Families who care for children with thalassemia will experience psychosocial problems. Ignorance is the reason why families find it difficult to adapt. Therefore, it is necessary to provide knowledge and the ability to adapt to stressors so that family coping is positive. This study aims to determine the effect of Family Psychoeducation on parents' coping strategies in caring for children with thalassemia. The research design used a